Dziedzictwo : ziemianie polscy i i udzial ich w zyciu narodu - Chrzanowski, Tadeusz (Krakow : Wydawn. Znak, 1995)
A collection of articles on the history of the Polish gentry and their impact on the nation during the hard days of the 19th and 20th centuries.
Summary in English.
Keywords: Gentry -- Poland -- History; Nobility -- Poland -- History